Generalized Continuous Functions from Any Topological - Boonpok, Chawalit (Asian Health, Science and Technology Reports, 2013)
In this paper we prove some relationship between continuous functions and g-continuous functions and study g-continuous functions from any topological spaces into product spaces. In general continuous functions is g-continuous functions but not conversely. We can give some characterizations of this type of continuity.